Countering Nationalist Politics Through Distant Witnessing: An Affective-Discursive Approach - Altman Yuzhu Peng; Yu Sun; Chunyan Wu (Social Media + Society)
Advancing an affective-discursive approach, this article examines how distant witnessing bolsters digital activist organizing that challenges a Southern authoritarian regime’s nationalist politics on international social media. The research foregrounds an initiative coordinated by a group of overseas dissidents who sought to expose China’s foreign policy regarding the Russian invasion of Ukraine on X (Twitter). Amid ongoing battlefield stalemates that have prolonged the war, this initiative has evolved into a broader form of resistance, staging distant witnessing through X postings to circumvent the party-state’s internet censorship. As this process unfolds, activists capitalize on social media affordances to curate witness testimonies that counter China’s distorted geopolitical narratives and beyond. Resorting to both pre-discursive and discursive gestures, this repertoire contributes to the formation of affective publics, thereby stimulating public contention over the party-state’s authoritarian rule from afar. The findings highlight how such digital platforms as X enable an informal model of organization, allowing Southern activists to act as mediators who coordinate distant witnessing in a transnational context.